Crack propagation analysis in composite materials by using moving mesh and multiscale techniques. (June 2015) - Greco, Fabrizio; Leonetti, Lorenzo; Lonetti, Paolo; Nevone Blasi, Paolo
Highlights: A novel multiscale method for crack propagation analysis in composites is proposed. An adaptive model refinement is used during crack propagation to improve efficiency. Competition between different damage mechanisms is handled during crack simulation. Matrix cracking is modeled by a novel optimization strategy based on moving meshes. The proposed approach is validated by original comparisons with existing methods. Abstract: A novel concurrent multiscale method for the crack propagation analysis in heterogeneous materials is proposed, based on a non-overlapping domain decomposition technique coupled with an adaptive zoom-in strategy. Both fiber/matrix interfacial debonding and matrix cracking are accounted for; the latter one is modeled by using an innovative shape optimization method coupling a moving mesh technique and a gradient-free optimization solver. Numerical applications are carried out with reference to the failure analysis of a single notched fiber-reinforced composite beam subjected to both mode-I and mixed-mode crack propagation conditions. The validity of the proposed method is assessed through original comparison models.